Peningkatan Keterampilan Praktik Shalat melalui Metode Demonstrasi pada Siswa Kelas 2 di MI Golempang - Lilis Lisnawati (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2023)
This study aims to improve students' prayer practice skills through the application of demonstration methods in Islamic Jurisprudence learning. The study was conducted in class 2 of MI Golempang using the Classroom Action Research (CAR) approach which was implemented in two cycles. Each cycle consists of planning, implementation, observation, and reflection stages. Data collection techniques were carried out through direct observation and literature studies. Based on the results of problem identification, it was found that there were still students who had difficulty in practicing prayer, both in terms of movement and reading. Through the application of the demonstration method, it is expected to be able to correct these errors so that the quality of students' prayer practice increases. The results of the study showed that the demonstration method was able to increase students' concentration in learning and direct the learning process more effectively.